(untitled) (Research, Society and Development, 2022)
Zamak is a Zn-Al-based metal alloy that has proven to be extremely versatile. This alloy has a low melting point and excellent fluidity, which makes it possible to obtain parts of complex geometry on a large scale, through the pressure casting process. However, the manufacturing process generates gaseous porosities inside the parts, which makes the alloy present a corrosion resistance lower than the minimum established by NBR 10283 regarding the surface of sanitary metals. The objective of this work is to characterize the surface of Zamak 5 injected under pressure after being subjected to the anodizing process. To carry out the proposed analysis, Zamak 5 samples were injected under pressure and subjected to different anodizing times: 20, 50, 110, 300, 1800 and 3600 seconds. The samples were analyzed with scanning electron microscopy (SEM), microhardness, roughness and potentiodynamic polarization assay. The results showed that the Zamak before the anodizing process presented greater corrosion resistance than after this treatment. This can be explained by the preparation process for anodizing, which makes the part more susceptible to corrosion and by the appearance of cracks and cracks that appeared with the anodizing process. However, among the anodized samples, the longer the anodizing time, the more noble its behavior became. It was found that the surface layer is composed of oxalates and oxides of zinc and aluminum. This surface layer showed an increase in hardness and surface roughness.